Perspektif Logikalisme dan Formalisme terhadap Pembelajaran Matematika Mindful, Meaningful, dan Joyful - Indra Tri Buana; Burhannurfirdaus Abdulah; Anggun Badu Kusuma (Griya Journal of Mathematics Education and Application, 2026)
21st-century mathematics education is not only oriented towards mastering concepts and procedures, but alsotowards developing mindful, meaningful, and joyful (MMM) learning experiences. In this context, thephilosophy of mathematics serves as a theoretical foundation that can provide direction for the developmentof more effective learning. This study aims to analyze the contribution of logicalism and formalismperspectives to MMM-based mathematics learning. The study used the Systematic Literature Review (SLR)method by reviewing various relevant literature from scientific journals, books, and other academic sources.Data were analyzed using content analysis techniques through the processes of identification, classification,interpretation, and synthesis of findings. The results of the study indicate that logicalism contributes todeveloping deductive reasoning skills, critical thinking, mathematical argumentation, and conceptualunderstanding that support the realization of meaningful learning. Meanwhile, formalism plays a role inbuilding procedural skills, accuracy, consistency, and awareness of thought processes that align with theprinciples of mindful learning. The integration of these two perspectives can create more reflective,systematic, and joyful mathematics learning. Thus, logicalism and formalism can be seen as complementaryphilosophical foundations in supporting the development of modern mathematics education.